Dual metal gate AlGaN/GaN high electron mobility transistors with improved transconductance and reduced short channel effects. (22nd December 2020) - Pinchbeck, Joseph; Lee, Kean Boon; Jiang, Sheng; Houston, Peter
Abstract: AlGaN/GaN high electron mobility transistors with a range of dual metal gate (DMG) lengths have been fabricated and studied. An improvement in transconductance up to 9% has been measured in the DMG devices in comparison to the conventional single metal gate devices. This is attributed to the distribution of the electric field under the gate region as a result of two gate metals. The drain induced barrier lowering is also suppressed using the sub- µ m DMG devices, with a drain induced barrier lowering decrease of around 50% due to a potential shielding effect in the two-dimensional electron gas channel.